TEMPERATURE-CARBON DIOXIDE PARTIAL PRESSURE TRENDS IN CONFINED AQUIFERS - Coudrain-Ribstein A.; Gouze P.; de Marsily G. (My University, 1998)
More than 500 published data of partial pressure of CO2 (PCO2) were collected for aqueous solutions from about 30 confined aquifers. The selection was limited to cases with no gas phase. Hence, with a temperature range for the data from 10°C to 300°C, the corresponding hydrostatic pressure is greater than a few bars to 100 bar, respectively. The data of PCO2 plotted as a function of temperature are clearly grouped into two exponential curves. The lower curve corresponds to a pure magmatic rock environment. The PCO2 varies from 10-6 to 50 bar when the temperature increases from 10°C to 300°C. The higher curve corresponds to a sedimentary environment. The PCO2 varies from 2 10-3 to 130 bar when the temperature increases from 10°C to 200°C. Such trends of PCO2 can be computed thermodynamically. The chemical species CO2 can be expressed as a relation including solely minerals (mj) and their stoichiometric coefficient (αj): CO2 # #jαjmjIf a solution is at equilibrium with respect to these minerals, the PCO2 value equals the product of their solubility products: PCO2 = #jKαjjKCO2This expression of PCO2 depends on temperature (mainly) and pressure (weakly) and is independent of any other solution characteristic such as chloride content. The seventeen sets of minerals tested can be divided into two generic sets: {calcite, Ca-Al-silicate, additional silicates} {calcite, dolomite, Mg-Al-silicate, other silicates}The ones including only one carbonate, calcite, fit the lower PCO2 data from magmatic rocks. The ones including two carbonates, calcite and dolomite, fit the higher PCO2 data from magmatic rocks. Although carbon in solution might have several origins (deep magmatic flux, decomposition of organic matter and dissolution of carbonate minerals), the PCO2 data are equal to the ones that would be buffered by the equilibrium of the solution with respect to a set of minerals. These results are of interest for the use of chemical geothermometers and for studies of changes in sediment porosity by diagenesis over geologic times. When modelling chemical evolution of a solution in a geologic formation, it is useful to test simulations including, among the chemical constraints, equilibrium with respect to some j minerals allowing the PCO2 value to be buffered.
Keywords: HYDROGEOCHEMISTRY; CONFINED ACQUIFERS; PARTIAL CO; CHEMICAL COMPONENTS